The Role of Caffeine on Swimming: A Literature Review - Paruhum Rico Yohanes (Eduvest - Journal of Universal Studies, 2024)
Caffeine is a widely recognized stimulant that affects the central nervous system and has garnered attention in sports, particularly swimming, for its potential to enhance physical performance. This literature review examines the complex relationship between caffeine consumption and swimming performance, focusing on factors such as dosage, timing, and individual responses. Evidence suggests that caffeine can improve sprint performance, with studies indicating a 2-3% increase in speed for short distances (50-100 meters) and a 1.5-2.0% reduction in times for mid-distance events (200-400 meters). Optimal caffeine intake ranges from 3-6 mg/kg body weight, consumed 30-60 minutes prior to competition, although excessive intake may lead to adverse effects. Individual variability, influenced by genetics and physiological conditions, plays a significant role in performance outcomes. While caffeine shows promise as an ergogenic aid, careful consideration of individual differences and potential side effects is essential. Further research is needed to refine understanding of caffeine's impact on swimming performance and to develop tailored recommendations for athletes and coaches.